1983
DOI: 10.1002/cne.902180209
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of GABA‐T‐Intensive neurons in the hat forebrain and midbrain

Abstract: The neuronal distribution of gamma-aminobutyric acid (GABA) transaminase (GABA-T), the enzyme which metabolizes GABA, has been mapped in rat brain. The method involves staining for newly synthesized GABA-T by the previously established nitro blue tetrazolium technique in animals killed 8-48 hours after administration of gabaculine, an irreversible inhibitor of GABA-T. Neuronal staining is obscured by staining of other elements if initial suppression is inadequate or survival times postgabaculine are too long. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(81 citation statements)
references
References 34 publications
8
72
0
1
Order By: Relevance
“…Projections from these nuclei are primarily GABAergic and peptidergic (Nagai et al, 1983;Oertel et al, 1983;Kalivas et al, 1993b;Sun and Cassell, 1993;Zahm et al, 2001a), with the most dense projection coming from the NAshell (Zahm et al, 2001b). However, the BNSTv also sends a glutamatergic projection to the VTA (Georges and Aston-Jones, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Projections from these nuclei are primarily GABAergic and peptidergic (Nagai et al, 1983;Oertel et al, 1983;Kalivas et al, 1993b;Sun and Cassell, 1993;Zahm et al, 2001a), with the most dense projection coming from the NAshell (Zahm et al, 2001b). However, the BNSTv also sends a glutamatergic projection to the VTA (Georges and Aston-Jones, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While immunohistochemical studies indicate that GABA-containing fibres can account for its presence within the s.o.n. itself, the distribution of GABAergic cells extends forward from the perinuclear area into and beyond the diagonal band (Nagai et al 1983;Panula et al 1984). We have recently reported (Jhamandas & Renaud, 1986) that diagonal band neurones projecting to s.o.n.…”
Section: Discussionmentioning
confidence: 99%
“…had no effect on the depression in VP neuronal activity following baroreceptor activation suggested that this response was mediated by another transmitter, possibly y-aminobutyric acid (GABA). The present study was further prompted by reports of immunoreactive GABAergic neurones in the diagonal band of Broca (Nagai, McGeer & McGeer, 1983;Panula, Revuelta, Cheney, Wu & Costa, 1984). In this area, we have noted enhanced firing of s.o.n.…”
Section: Introductionmentioning
confidence: 93%
“…They concluded that the distribution of GABA-T-intensive neurons in the rat brain was convincing evidence for the correspondence of GABA-T-intensive and GABA neurons (15,17) . Although they observed a few GABA-T-intensive neurons in the so area, they did not describe them in detail (16).…”
mentioning
confidence: 99%
“…Recently, Nagai et al (17) introduced a pharmaco-histochemical method with gabaculine treatment for selectively detecting GABA-T-positive neuronal perikarya. They concluded that the distribution of GABA-T-intensive neurons in the rat brain was convincing evidence for the correspondence of GABA-T-intensive and GABA neurons (15,17) .…”
mentioning
confidence: 99%